Physical activity and neuroinflammation: a bibliometric analysis of research progress and future perspectives - Yeting Zhang; Huangyan Li; Jiangxi Yang; Huan Ma (Frontiers in Aging Neuroscience)
BackgroundNeuroinflammation is a common pathological feature of neurodegenerative and psychiatric diseases and is closely related to the dysfunction of the nervous system. In recent years, an increasing number of studies have shown that physical activity (PA) has a significant regulatory effect on neuroinflammation. However, a comprehensive analysis of research in this field is currently lacking, including the evolution of knowledge structures, interdisciplinary trends, and dynamic shifts in research hotspots.MethodsThis study retrieved relevant literature from the Web of Science Core Collection database for the period from 2004 to 2025. The search strategy was TS = ((“physical activit*” OR exercis* OR “exercise training”) AND (“neuroinflammat*” OR “neuro inflammatory” OR “neuro-inflammatory”)), with the document type limited to Articles and Reviews. After screening, a total of 661 eligible articles were included for bibliometric analysis. The analysis tools used were the Bibliometrix R package and VOSviewer, which were employed to visualize the results of the literature analysis.ResultsFrom 2004 to 2025, the number of publications in this field showed a yearly increasing trend, with an annual growth rate of 15.05%. China and the United States were the main contributing countries, publishing 122 and 111 articles, respectively. In terms of journals, the International Journal of Molecular Sciences ranked first with 36 articles and a total of 799 citations. Among the institutions, Karolinska Institute led the way in terms of citation counts, amassing a total of 391 citations. Regarding author keywords, “Alzheimer’s disease,” “microglia,” and “older adults” were the three most frequently occurring keywords. Research hotspots have gradually shifted from the early focus on hippocampal function and neuroinflammation mechanisms to current directions such as neurodegenerative diseases, microglial regulation, and the gut–brain axis.ConclusionThis study systematically reviewed the research progress in the field of PA and neuroinflammation from 2004 to 2025 using bibliometric methods and revealed the research hotspots, trends, and thematic evolution in this field. It provides a systematic scientific basis for scholars to understand the field, optimize research directions, and develop intervention strategies.